A combined tuned damper and an optimal design method for wind‐induced vibration control for super tall buildings. (20th January 2016) - Wang, Lilin; Zhao, Xin; Zheng, Yimin M.
Summary: The wind‐induced vibrations of super tall buildings become excessive due to strong wind loads, super building height and high flexibility. Tuned mass dampers (TMDs) and tuned liquid column dampers (TLCDs) have been widely used to control vibrations for actual super tall buildings for decades. To fully use both the economic advantage of the TLCD system and the high efficiency of the TMD system, an innovative supplemental damping system including both TLCD and TMD and called combined tuned damper (CTD), which can substantially decrease the cost of the damper, was proposed to control the wind‐induced vibrations of tall buildings. The governing equations are generated for the motion of both the primary structure and the CTD and solved to anticipate the dynamic response of the CTD‐structure system. Moreover, an optimal design method of human comfort performance is proposed, in which the life cycle cost of the damper‐structure system is considered as the quantitative index of the performance. The life cycle cost includes the initial cost, the maintenance cost and the failure cost. The failure cost can be calculated using the vibration‐sensation rate model, which is based on the Japanese code AIJES‐V001‐2004. Copyright © 2016 John Wiley & Sons, Ltd.